The Influence of Infrastructure on Village Community Income (Ujung Rambung, Kecamatan Pantai Cermin, Serdang Bedagai Regency) - Elvira, Ilda Agus; Lidia Yunita (Journal of Economics and Business (JECOMBI), 2022)
Research is carried out in the village of Ujung Rambung District of Coast Mirror Regency of Serdang Bedagai , research is aimed to determine the effect of the construction of infrastructure roads, infrastructure drainage and infrastructure TPT against income communities village End Rambung District of Coast Mirror District Serdang Bedagai. Type of research this is quantitative with approach to research descriptive and associative researchers using SPSS 16 for test research. The samples in the study is that 100 respondents Society Village Edge Rambung District of Coast Mirror Regency of Serdang Bedagai the results obtained by using the formula solvin. Sources of research data using primary data and secondary data, data collection techniques used interviews, questionnaires and literature study. Mechanical analysis of the data using test validity, test reliability, test the assumptions of classical use test for normality, test of heteroscedasticit, a test multicollinearity, test linear multiple and test hypotheses are partial and simultaneous results of the study provide answers to the hypothesis, that ariable construction of infrastructure roads, Infrastructure Drainage and Infrastructure TPT affect income communities village of is 0828 or 82.8% and the remaining 17.2% can be explained by variables other.